SCENARIO PLANNING OF THE CUSTOMER ORIENTATION OF THE COMPANY - Stankovska I. М.; Shyptur , O. V.; Stankovskyi , T. V. (The actual problems of regional economy development, 2022)
Customer orientation is a key factor for strong competitive position of the enterprise. This notion has become particularly relevant for gas utilities in recent years (due to the introduction of competition in the gas market). These changes not only forced enterprises to change their approach to operations but also demonstrated that even monopoly markets, which are used to complete stability, today will require significant reorganization and unpredictable changes. Scenario planning itself is crucial for the prevention and prediction of external instability. An analysis of the development of customer orientation of the gas distribution company, substantiation of feasibility of implementation of measures for increasing of level of its customer orientation. This scientific work formulates the definition of " customer orientation ", " customer orientation"; analyzes the current methods of assessing the level of client orientation; examination of the features of scenario planning as one of the basic technologies of strategic management; analyzed and evaluated the level of clientorientation of «Ivano-Frankivskgas» joint-stock company, create scenarios of development of the company's customer orientation, the efficiency of each of the proposed alternatives is investigated and the scenario of implementation of modern methods of training in the company as the most probable and effective alternative for the development of customer orientation of «Ivano-Frankivskgas» is outlined. On the basis of the conducted scientific researches and published scientific works the customer orientation, as one of the main ways for providing competitiveness of "Ivano-Frankivskgas" was determined. For realization of the mentioned tasks analysis and synthesis methods, NPS index method, decision trees method, analytical and graphical methods, line forecasting method and method of scientific generalization were used. The scientific novelty of the results are as follows: - Application of methods of scenario planning for choosing and realization of ways of providing customer orientation of gas supplying enterprises is suggested. Practical relevance of the results obtained has been further developed in: - assessment of customer orientation of «Ivano-Frankivskgas» by means of the index NPS calculated based on the results of the questionnaire; - development of scenarios of customer orientation development for «Ivano-Frankivskgas»; - application of «decision trees» method for forming scenarios of customer orientation development of Ivano-Frankivskgas.